CONSTRUCTING ECOTOURISM-BASED BUSINESS COMPETENCY AND ENTREPRENEURAL SPIRIT - Ni Nyoman Aryaningsih; Ketut Irianto; I Made Marsa Arsana; I Nyoman Meirejeki (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
Ecotourism is a part of a tourism development as a catalisator of the economy in rural areas in Bali, Indonesia. It is established in rural areas as an effort to improve the quality of life and social identity and to give employment opportunities, income, education and skills, cultural understanding, and to bring the development of entrepreneurial spirit and community welfare. The contribution of income from ecotourism ranges from 15 to 57%, with an average of 12.6% per year. As the title implied, this explorative study with a semantic analysis is done to construct ecotourism-based business competencies and entrepreneural spirit. Primary and secondary data analysis are used through survey and interview. Ecotourism-based business competence can be formed by the community behavior in protecting the natural resources, such as forest as water buffer, entrepreneurship development. The formation of internal competence through the perspective, experience, education, learning by 80% and very dominant influence external competence in the group that can produce human capital. The proportion of internal competence attached to individuals has a very high strength compared to external competencies in ecotourism support services. Internal competence and external competence as the basis of business competence is crucial to the development and sustainability of ecotourism as the basis for developing tourist village. Building an understanding of business competence and entrepreneurial spirit in the development of tourist villages such as ecotourism is expected to have a positive impact to improve the welfare of rural communities